The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s12864-021-07464-x
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptomic responses of Atlantic salmon (Salmo salar) to high temperature stress alone, and in combination with moderate hypoxia

Abstract: Background Increases in ocean temperatures and in the frequency and severity of hypoxic events are expected with climate change, and may become a challenge for cultured Atlantic salmon and negatively affect their growth, immunology and welfare. Thus, we examined how an incremental temperature increase alone (Warm & Normoxic-WN: 12 → 20 °C; 1 °C week− 1), and in combination with moderate hypoxia (Warm & Hypoxic-WH: ~ 70% air saturation), impacted the salmon’s hepatic transcriptome expr\e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 141 publications
(143 reference statements)
5
47
2
1
Order By: Relevance
“…Our data, in combination with other recently published data (Gamperl et al, 2020 ; Zanuzzo et al, 2020 ; Beemelmanns et al, 2021a , b , c ; and see references above), also provide vital/key new information on how conditions at salmon cage-sites during the summer/early fall are likely to impact these fish in Atlantic Canada and suggest that a multi-faceted approach may/will be needed to prevent potential losses at salmon cage-sites under current climate change scenarios (see IPCC, 2019 ). Given recent data which suggest that Atlantic salmon of Saint John River stock can survive long-term exposure to temperatures of > 21°C in combination with moderate hypoxia (60–70% air saturation) and that unlike fish in Tasmania (Stehfest et al, 2017 ; Wade et al, 2019 ) have not yet experienced these temperatures, it is clear that selective breeding for upper thermal tolerance (given its effects on food consumption, growth, and stress biomarkers; Gamperl et al, 2020 ; Beemelmanns et al, 2021a , b ) is not only needed to improve production in the summer and to prevent losses that are predicted to get worse given rising average ocean temperatures and more frequent/severe heat waves. Better vaccines against bacterial and viral diseases and mitigating strategies/treatments for pathogen outbreaks (incl.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data, in combination with other recently published data (Gamperl et al, 2020 ; Zanuzzo et al, 2020 ; Beemelmanns et al, 2021a , b , c ; and see references above), also provide vital/key new information on how conditions at salmon cage-sites during the summer/early fall are likely to impact these fish in Atlantic Canada and suggest that a multi-faceted approach may/will be needed to prevent potential losses at salmon cage-sites under current climate change scenarios (see IPCC, 2019 ). Given recent data which suggest that Atlantic salmon of Saint John River stock can survive long-term exposure to temperatures of > 21°C in combination with moderate hypoxia (60–70% air saturation) and that unlike fish in Tasmania (Stehfest et al, 2017 ; Wade et al, 2019 ) have not yet experienced these temperatures, it is clear that selective breeding for upper thermal tolerance (given its effects on food consumption, growth, and stress biomarkers; Gamperl et al, 2020 ; Beemelmanns et al, 2021a , b ) is not only needed to improve production in the summer and to prevent losses that are predicted to get worse given rising average ocean temperatures and more frequent/severe heat waves. Better vaccines against bacterial and viral diseases and mitigating strategies/treatments for pathogen outbreaks (incl.…”
Section: Discussionsupporting
confidence: 91%
“…A report commissioned to determine the cause of the mortalities (Burke et al, 2020 ) concluded that these environmental conditions were the primary cause of the large number of salmon deaths. However, more recent data on the effects of these conditions on fish physiology (Gamperl et al, 2020 , Zanuzzo et al, 2020 ; Beemelmanns et al, 2021a , b , c ), and contained in this study, do not support this assertion. For example, the salmon in the cage in which we had fish did not experience temperatures > 19.5°C; large (> 800 g) salmon from similar stocks have been shown to tolerate elevated temperatures as high as 21°C for prolonged periods when combined with water O 2 levels of 60–70% saturation (lower than the lowest O 2 levels reported in the cages) without mortalities (Gamperl et al, 2020 ); salmon from Norway and Tasmania can tolerate prolonged exposure to similar temperatures (Hvas et al, 2017 ; Tromp et al, 2018 ); the critical oxygen tension/limiting oxygen saturation (LOS) for Atlantic salmon is ~63–67% at 22°C (Barnes et al, 2011 ; Remen et al, 2013 ), well below the water oxygen level reported in the cages by Burke et al ( 2020 ); and all the salmon implanted with data loggers that survived for several weeks post-implantation experienced similar conditions to those reported in the summer of 2019.…”
Section: Discussioncontrasting
confidence: 79%
“…Our results suggest a potential role of HSPs in the immune system of sea cucumber coelomocytes under HS. Similar results have also been reported in some fish species such as rainbow trout Oncorhynchus mykiss (Huang et al, 2018) and Atlantic salmon Salmo salar (Beemelmanns et al, 2021).…”
Section: Immune Responsesupporting
confidence: 89%
“…In Oncorhynchus kisutch, hypoxia generated a cortisol stress response ≤35% DO levels and several toll-like receptors and cytokines of the innate and adaptive immune response were differentially regulated (Martínez et al, 2020). Transcriptome analyses revealed combined effects of hypoxia and high water temperature (20 • C) on hepatic expression of immune and stress genes in Atlantic salmon (Beemelmanns et al, 2021).…”
Section: Introductionmentioning
confidence: 99%